Potential effect of pharmacogenetics on maternal, fetal and infant antiretroviral drug exposure during pregnancy and breastfeeding - Adeniyi Olagunju (2018)
Mother-to-child-transmission rates of HIV in the absence of any intervention range between 20 and 45%. However, the provision of antiretroviral drugs (ARVs) during pregnancy, delivery and breastfeeding can reduce HIV transmission to less than 2%. Physiological changes during pregnancy can influence ARV disposition. Associations between SNPs in genes coding for metabolizing enzymes, and/or transporters, and ARVs disposition are well described; however, relatively little is known about the influence of these SNPs on ARV pharmacokinetics during pregnancy and lactation as well as their effect on distribution into the fetal compartment and breast milk excretion. Differences in maternal, fetal and infant ARV exposure due to SNPs may affect the efficacy and safety of ARVs used to prevent mother-to-child-transmission. The aim of this review is to provide an update on the effect of pregnancy-induced changes on the pharmacokinetics of ARVs and highlight the potential role of pharmacogenetics. © 2012 Future Medicine Ltd.